2016
DOI: 10.1016/j.ejmech.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Design of a novel thiophene inhibitor of 15-lipoxygenase-1 with both anti-inflammatory and neuroprotective properties

Abstract: The enzyme 15-lipoxygenase-1 (15-LOX-1) plays a dual role in diseases with an inflammatory component. On one hand 15-LOX-1 plays a role in pro-inflammatory gene expression and on the other hand it has been shown to be involved in central nervous system (CNS) disorders by its ability to mediate oxidative stress and damage of mitochondrial membranes under hypoxic conditions. In order to further explore applications in the CNS, novel 15-LOX-1 inhibitors with favorable physicochemical properties need to be develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 57 publications
(49 reference statements)
0
28
0
Order By: Relevance
“…From the pharmacological point of view, the analysed 1,3,4-tiadiazoles [ 5 , 6 ] substituted with the resorcylic fragment have been observed to have promising anticancer [ 7 , 8 , 9 , 10 ] and neuroprotective [ 11 , 12 , 13 ], anti-oxidative [ 7 ], antifungal and antibacterial activities [ 14 , 15 , 16 , 17 ], anti-inflammatory [ 18 ]. They also show certain very interesting properties as a group of ligands capable of forming complexes with selected D-block metals [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the pharmacological point of view, the analysed 1,3,4-tiadiazoles [ 5 , 6 ] substituted with the resorcylic fragment have been observed to have promising anticancer [ 7 , 8 , 9 , 10 ] and neuroprotective [ 11 , 12 , 13 ], anti-oxidative [ 7 ], antifungal and antibacterial activities [ 14 , 15 , 16 , 17 ], anti-inflammatory [ 18 ]. They also show certain very interesting properties as a group of ligands capable of forming complexes with selected D-block metals [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we provide a new strategy to find the potential effective drug target combinations of all three types of drug target combinations involved in our paper. Among the combinations of drug targets we have screened, there are five combinations have been proven to be viable by the corresponding biological experiments, including the combination of 5-LOX and 12-LOX [26], combination of 5-LOX and LTA4H [27], combination of 15-LOX and PLA2 [28], combination of PLA2 and LTA4H [29, 31, 32] and combination of PLA2 and 5-LOX [30]. What’s more, if we can combine the price and doses of drugs, we can have a better optimization.…”
Section: Resultsmentioning
confidence: 99%
“…4. There are thee combinations have been proven to be viable by the corresponding biological experiments, including the combination of 15-LOX and PLA2 [28], combination of PLA2 and LTA4H [29], and combination of PLA2 and 5-LOX [30]. Especially, it has been found that pathway including PLA2 and LTA4H in AA metabolic network is very important for traditional Chinese medicine anti-inflammatory herbal formulae and the treatment of cancers [29, 31, 32].…”
Section: Applying the Strategy Of Screening Drug Target Combinations mentioning
confidence: 99%
“…The reason for this dearth of LOX therapeutics in general is multifaceted, but two limitations in the advancement of LOX-targeting anti-inflammatory inhibitors has been the characterization of the specific role of each LOX isozyme and the difficulty in identifying/developing isoform-selective inhibitors. However, with recent successes, this issue is slowly being overcome [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%